Tracking Familial History of Reading and Math Difficulties in Children’s Academic Outcomes - Nguyen, Tin Q.; Martinez-Lincoln, Amanda; Cutting, Laurie E. (Frontiers in Psychology, 2022)
The current study aimed to investigate the extent to which familial history of reading and math difficulties have an impact on children’s academic outcomes within a three-year longitudinal study, which evaluated their core reading and math skills after first (N = 198; 53% girls) and second grades (N = 166), as well as performance on complex academic tasks after second and third grades (N = 148). At baseline, parents were asked to complete the Adult Reading History Questionnaire (ARHQ) and its adaption, Adult Math History Questionnaire (AMHQ), to index familial history of reading and math difficulties, respectively. Preliminary findings established the psychometric properties of the AMHQ, suggesting that it is a reliable and valid scale. Correlation analyses indicated that the ARHQ was negatively associated with children’s reading skills, whereas the AMHQ was negatively related to math outcomes. Path results revealed that the ARHQ predicted children’s performance on complex reading tasks indirectly via their core reading skills, and the AMHQ was linked to complex math outcomes indirectly via core math abilities. The ARHQ was also found to be negatively correlated with measures of children’s math performance, with path findings suggesting that these relations were indirectly explained by differences in their core reading skills. These results suggest that assessing familial risk for academic difficulties may be crucial to understanding comorbid etiological and developmental associations between reading and math differences.